Synergistic effects of shoulder functional training and injury cognition education on shoulder injury prevention among young chinese tennis players from a social cognitive perspective - Pengju Xie; Nur Shakila Mazalan; Denise Koh Choon Lian (Environment and Social Psychology, 2025)
Objective: To explore the synergistic effects and underlying mechanisms of shoulder functional training and injury cognition education on shoulder injury prevention among Chinese young tennis players based on social cognitive theory. Given that factors such as coach authority status, mentor-mentee relationship patterns, and team cohesion in the Chinese collectivist cultural context may significantly influence preventive behaviors, and existing research is mostly based on Western individualistic cultural backgrounds, this study focuses on the uniqueness of the Chinese context, aiming to reveal culturally sensitive injury prevention mechanisms. Methods: Using a cluster randomized controlled trial design, 120 young tennis players from 8 training bases were randomly allocated to a shoulder functional training group, an injury cognition education group, a combined intervention group, and a control group, receiving 12-week interventions with 3-month follow-up. Multiple dimensional indicators were measured, including shoulder joint function, psychological cognitive variables (self-efficacy, outcome expectations, risk perception), social support (coach support, peer influence, team culture), and preventive behaviors. Results: The combined intervention group showed superior outcomes. Its comprehensive effect index (0.91±0.07) significantly exceeded those of single-intervention groups. The synergistic enhancement index reached 1.42. The injury incidence rate dropped to 6.7%. The maintenance rate of preventive behaviors reached 91.2%. Self-efficacy demonstrated a mediation effect that accounted for 56.6% of the total effect. The dual cognitive mechanism of outcome expectation and risk perception jointly explained 47.3% of the variance in preventive behaviors. Cognition and behavior exhibited a dynamic, upward spiral pattern of interaction. Coach support (β=0.42) and peer influence (β=0.38) significantly moderated intervention effects. Team-level factors explained 28% of behavioral variance. Conclusion: Shoulder functional training and injury cognition education produce significant synergistic effects. Self-efficacy, outcome expectation, and risk perception constitute the cognitive mediation mechanism. Coach support and team culture play critical moderating roles in the Chinese context. These findings provide theoretical foundation and practical guidance for developing localized injury prevention systems.